Perbuatan pidana kesusilaan dalam rancangan undang-undang KUHP - Sri Hartini (Universitas Negeri Yogyakarta, 2004)
As an independent and sovereignty country, Indonesia should arrange KUHP (Kitab Undang-Undang Hukum Pidana) to avoid loss of criminalities that have been increasing. The renewal of KUHP is very needed because it's not proper with the values of social politic, social philosophy, and social cultural of Indonesia people. It is the basic for sosial, criminal policy, and law enforcement. The urgency of revising of KUHP, specially putting susila crime put in draft criminal code (RUU KUHP) and almost the requirement still be formed widely, not distinguishing between criminal and people who break the rule, but the words